DIGITAL MICROFINANCE PLATFORMS ON FINANCIAL INCLUSION IN POST-CONFLICT REGIONS WITHIN THE MIDDLE EAST AND NORTH AFRICA - JOSEPH OLORUNFEMI AKANDE (International Studies Journal)
This study investigates the transformative potential of digital microfinance platforms in advancing financial inclusion across conflict-affected communities in the Middle East and North Africa (MENA) region, where conventional banking infrastructure remains largely inaccessible. Focusing on Syria, Iraq, and Lebanon as representative cases, the research employs quantitative analysis of survey data collected from 300 adult respondents to evaluate how technological accessibility, digital literacy levels, socioeconomic barriers, and gender dynamics influence adoption patterns. The analysis reveals that intuitive platform interfaces combined with targeted financial education initiatives significantly enhance service uptake, while persistent affordability constraints and culturally embedded gender disparities continue to impede equitable access. Notably, the study identifies a critical need for localized adaptation of digital financial solutions to address the unique challenges of populations grappling with displacement and fragmented institutional support systems. These findings contribute to ongoing policy discussions about leveraging financial technology for economic recovery in post-conflict scenarios. As a primary recommendation, the study advocates for integrated intervention models that combine low-cost mobile banking platforms with community-based financial capability programs, particularly those designed to empower female entrepreneurs and displaced persons. The research underscores the importance of multi-stakeholder collaboration between fintech developers, humanitarian agencies, and local governance structures to create sustainable financial ecosystems in fragile contexts.